Hoya peninsularis (Apocynaceae, Asclepiadoideae), a new species from Peninsular Malaysia, and notes on Hoya maingayi and Gongronema wrayi. (23rd October 2020) - Rodda, Michele; Zakaria, Rahmad
Abstract : A new species of Hoya from the western part of Peninsular Malaysia is described and illustrated as H. peninsularis . It has long been confused with Hoya finlaysonii because both have leaves with prominent darker venation, but can be distinguished on the corona lobe size and corolla pubescence. In addition, Hoya maingayi, a species earlier considered 'doubtful and excluded' is typified and illustrated for the first time, and its distribution is shown to extend to Thailand. Gongronema wrayi is recognised as an earlier name and a new synonym for Hoya omlorii, a species previously considered to occur only in Borneo and Sumatra. The name is typified. An updated checklist of Hoya of Peninsular Malaysia is provided.